2014
DOI: 10.1590/1413-78522014220400860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic study on open fractures caused by motorcycle traffic accidents

Abstract: OBJECTIVE: To assess socio-demographic characteristics of individuals that suffered open fractures caused by motorcycle traffic accident and evaluate infection rate in search of associated risk factors. METHODS: A retrospective study comprising 81 patients with open fractures caused by motorcycle accidents was carried out. Clinic and socio-demographic features were collected from patients' records. Comparison between infected and non-infected patients was performed to find out which variables were possibly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
3
2
3
Order By: Relevance
“…Type III fractures of the Gustilo and Anderson classification were prevalent (46.70%), data that is common in previous studies of open fractures. 15 , 16 For the other fracture types, the values found were also similar to those reported in the literature, of 15.80% for type I, and 29.50% for type II. 15 …”
Section: Discussionsupporting
confidence: 89%
“…Type III fractures of the Gustilo and Anderson classification were prevalent (46.70%), data that is common in previous studies of open fractures. 15 , 16 For the other fracture types, the values found were also similar to those reported in the literature, of 15.80% for type I, and 29.50% for type II. 15 …”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the percentage of early infections (first 7 days) was 7.4%, results that differ from those of other studies from the national literature, which found percentages of 13.24%, 18.80%, and 23.7% for open fractures in general (18)(19)(20) , and most infections were observed in open fractures classified as Gustilo and Anderson type III (18)(19)(20)(21)(22) . It is inferred that our results were lower than those observed in the literature due to the higher percentage of less severe fractures in the current study (42% of Gustilo and Anderson type II open fractures); additionally, most study were prospective, with follow-up duration longer than 6 weeks (18)(19)(20)(21)(22) . In the study with the highest percentage of infections (23.7%), it was found that this high percentage was associated with severity of soft tissue injuries and delayed orthopedic treatment (22) .…”
Section: Discussioncontrasting
confidence: 99%
“…As informações obtidas dos 66 indivíduos internados com lesões traumáticas em membros inferiores, possibilitaram descrever as características sociodemográficas deste grupo e identificar os prováveis elementos centrais, intermediários e periféricos das representações sociais. Dos participantes da pesquisa 81,8% eram do gênero masculino, 81,9% tinham média de idade e desvio padrão 40,3 (18,5) (10)(11)(12) . Maior frequência de indivíduos com baixa escolaridade, renda mensal de até 1 salário mínimo, inseridos informalmente no mercado de trabalho, e o agente causador da fratura mais comum foi o uso da motocicleta, dados semelhantes ao estudo (13) , que observou uma alta prevalência de acidentes com motociclistas sugerindo um período de transição econômica próprio de países em desenvolvimento, com aumento de vítimas vulneráveis, oriundas da crescente classe média que adquire veículos motorizados particulares e com menor custo.…”
Section: Caracterização Dos Sujeitosunclassified
“…Observou-se, também, mudanças abruptas na saúde e no estilo de vida devido à lesões, agente causador de estresse emocional individual e familiar (15)(16)(17) . As fraturas expostas envolvendo a perna, tíbia e fíbula foram as mais frequentes, característica corroborada em estudo (18) , que encontrou maior frequência entre os pacientes com fraturas expostas por acidente de motocicleta em sua maioria homens, jovens, solteiros, com prevalência de lesões graves que acometeram a região da perna com infecção em 23.7% dos casos, fator associado à idade, tempo de exposição e à gravidade da lesão.…”
Section: Caracterização Dos Sujeitosunclassified
See 1 more Smart Citation